(untitled) (International journal of artificial intelligence, 2024)
This article explores the significance of interactivity and feedback in electronic learning (e-learning) and their impact on learner engagement, motivation, and overall learning outcomes. As e-learning continues to grow as a dominant mode of education, understanding how interactive elements and feedback mechanisms contribute to effective learning is essential. The article discusses how interactivity enhances learner engagement through tools such as quizzes, simulations, and collaborative projects, while feedback provides essential reinforcement and guidance. By combining these elements, e-learning platforms create personalized, dynamic, and learner-centered environments that foster deeper understanding, motivation, and continuous improvement. The article highlights the importance of these pedagogical components in ensuring the success of e-learning systems and in optimizing the learning experience for diverse student populations.